Subcutaneous nodules: an important adverse event following immunization - Rowena Silcock; Nigel W Crawford; Kirsten P Perrett (Taylor & Francis Group, 2019)
Introduction: Subcutaneous nodules are a rare adverse event following immunization (AEFI). Reported cases have frequently been associated with aluminum-containing vaccines. Despite the development of a consensus definition of a subcutaneous nodule from the Brighton Collaboration in 2004, there continues to be variation in definitions used in published literature. Areas covered: We reviewed the literature regarding subcutaneous nodule etiology, definition, clinical features, management, and approach to future immunizations. Embase and MEDLINE databases were searched with relevant MeSH terms initially on 8 November 2016, the same searches were repeated on 9 September 2018 prior to finalizing this review. We reviewed published case reports and larger studies reporting subcutaneous nodules and also reviewed articles discussing broader use of aluminum in immunizations and AEFIs. Expert commentary: Consensus from clinicians regarding the approach to management of subcutaneous nodules is vital. We believe that the safety concerns regarding aluminum causing subcutaneous nodules are far outweighed by the benefits of vaccines containing aluminum. Ultimately, supporting subsequent immunizations in individuals that develop nodules needs to be a priority.